INFLUENCE OF THE MILK FORMULA ENRICHED WITH BIFIDOBACTERIA STRAIN BB12 ON DEVELOPMENT OF INTESTINAL MICROFLORA IN NEWBORNS - E. V. Kulagina; Z. A. Chernaya; A. N. Shkoporov; E. V. Khokhlova; B. V. Efimov; Yu. M. Golubtsova; L. I. Kafarskaya ("Paediatrician" Publishers LLC, 2012)
The study deals with qualitative and quantitative structure of normal intestinal microflora in newborns before and after feeding with the formula «Agusha Gold 1» containing the strain B. lactis BB12. The specific structure of the intestinal bifidobacreria is studied in detail by means of the real-time polymerase chain reaction. It was demonstrated, that during the feeding with this formula there was a tendency towards development of the microbiota and specific structure of the intestinal bifidobacteria similar to those of the breast-fed children.